2015
DOI: 10.1016/j.agrformet.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Covariation between gross primary production and ecosystem respiration across space and the underlying mechanisms: A global synthesis

Abstract: a b s t r a c tGross primary production (GPP) and ecosystem respiration (RE) are two important processes in the terrestrial carbon cycle. Understanding the relationships between GPP and RE across space, as well as the underlying mechanisms, is helpful for understanding the terrestrial carbon cycle and predicting the global carbon budget. In this study, we investigated the correlation between the spatial variations in GPP and RE by compiling carbon flux data from 264 sites across the Asian, European, North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 69 publications
0
57
3
Order By: Relevance
“…Mass conservation precludes the driest sites from functioning indefinitely as carbon sources, and caution should be applied in extrapolating these results, which represent a period of drought in southwestern North America (Seager & Vecchi, ; Scott et al ., ). Drought may shift a number of long‐lasting constraints such as plant community and soil carbon pools, possibly reducing GEP and increasing R eco (Van der Molen et al ., ), similar to the ‘disturbance offset’ suggested in other multisite flux data syntheses (Baldocchi, ; Chen et al ., ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Mass conservation precludes the driest sites from functioning indefinitely as carbon sources, and caution should be applied in extrapolating these results, which represent a period of drought in southwestern North America (Seager & Vecchi, ; Scott et al ., ). Drought may shift a number of long‐lasting constraints such as plant community and soil carbon pools, possibly reducing GEP and increasing R eco (Van der Molen et al ., ), similar to the ‘disturbance offset’ suggested in other multisite flux data syntheses (Baldocchi, ; Chen et al ., ).…”
Section: Discussionmentioning
confidence: 82%
“…The spatial slope of R eco to GEP (0.64) for southwest North American semiarid ecosystems (Fig. ) was smaller than that reported in several prior studies (~0.7–0.9) (Law et al ., ; Baldocchi, ; Lasslop et al ., ; Chen et al ., ). It was more similar to that found in a recent synthesis across eddy covariance sites in China (0.68) with greater representation of semiarid ecosystems (Yu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A few reports have contended that spatial patterns of R s may be controlled more by photosynthesis and productivity than by soil temperature [4], [24], [25], [26]. Temporal patterns of R s have been simulated using continuous records of temperature, moisture, and other variables [12], [27], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with methods for estimating the temporal variation of R s , methods for quantifying spatial variation of R s are limited and difficult [30]. The spatial difference in R s within a site and between sites is often not explained by climatic variables; instead, the difference is modulated by gradients in the biological activity and differences in the soil properties [26], [27], [31], [32]. These features may provide a basis to design field experiments and conduct data analysis to improve the estimation of soil CO 2 emission from an ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Integrative analysis of global carbon fluxes data showed that GPP and RE co-varied at the spatial pattern from regional to global scale (Yu et al, 2013b;Chen et al, 2013;Chen et al, 2015b) . The spatial pattern of GPP determined 90% of the global spatial pattern of RE and its underlying physiological mechanism due to the fact that production GPP functions as the direct substrate provider for respiration RE (Chen et al, 2015b).…”
Section: High Carbon Sinks and Interrelations Among Carbon Fluxes At mentioning
confidence: 99%